Cegah Diabetes Melitus Tipe 2 Dengan "Sedia-Ubayahi" (Senam Diabetik & Ubah Gaya Hidup): Prevent Type 2 Diabetes Mellitus with “Sedia-Ubayahi” (Diabetic Gymnastics) & Lifestyle Change) - Lenny Rosbi Rimbun; Yudha Anggit Jiwantoro; Maryati (NERS Jurnal Keperawatan, 2020)
Diabetes mellitus is a disease characterized by high blood sugar levels. Basically, this happens because the body lacks the hormone insulin produced by the pancreas gland. It is therefore important to achieve and maintain metabolic control to prevent an increased risk of microvascular and macrovascular complications and lack of glycemic control. The purpose of this study is to analyze the effect of diabetes exercise therapy and lifestyle on blood sugar levels. Pre-experimental research design which is a research design that tests interventions in groups without involving control variables. The research design uses one postest postest design. The sample of the study were 40 respondents who met the inclusion and exclusion criteria. Test analysis using paired t test. The results showed that there was an influence of diabetes exercises and lifestyle (diet and activity) on blood sugar levels with a value of p (0,000). The conclusion that diabetic exercise and changing a healthy lifestyle can significantly control blood sugar levels.